The beast within - Salisbury, Joyce E., author.
1 online resource
Keywords: "The third edition of The Beast Within has been updated throughout to include current scholarship, new discussion of definitions, and fresh perspectives on critical animal theory that places animals, rather than humans, at the center of the discourse. With an interdisciplinary approach that discusses humans and animals in relation to domestication, symbolism, science, law, religion, food and diet, sexuality, and entertainment, The Beast Within is an essential resource for all students of animal history, literature, and art in the Middle Ages"--